Proceedings of the 1st International Conference on Innovation in Education (ICoIE 2018) 2019
DOI: 10.2991/icoie-18.2019.7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parents in Sundanese Language Preservation

Abstract: This paper presents one of the results of research on "A Need Analysis of Mother Tongue Program Development 2013."The study aimed to describe the efforts of parents in the preservation of the Sundanese language as a native language and a local language. The description of this paper includes the use of Sundanese language in everyday life at home and its surrounding environment; in communication with teachers at school; the importance of instilling manners of speaking (undak-usuk/unggah-ungguh) to children; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Moreover, a previous study [16] showed that the Sundanese language remains the main communication tool for adults and parents living in those regions. In the same paper, the authors concluded that there is a desire to preserve the Sundanese language in the fast-growing modern technological world as a cultural identity of the people.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous study [16] showed that the Sundanese language remains the main communication tool for adults and parents living in those regions. In the same paper, the authors concluded that there is a desire to preserve the Sundanese language in the fast-growing modern technological world as a cultural identity of the people.…”
Section: Introductionmentioning
confidence: 99%